(untitled) (Journal Of Educational and Psychological Researches, 2024)
The research aims to examine the misuse of technology in electronic relationships among students at Al-Mustansiriya University and to examine the significance of individual differences in the misuse of technology in electronic relationships among Al-Mustansiriya University students according to gender, class, specialization, and what is the most widely used means of social media (Facebook, Instagram, Twitter). Among the students of Al-Mustansiriya University, the current research focuses on the students of Al-Mustansiriya University in the morning study for the academic year (2021-2022). The research sample consisted of 300 male and female students from the College of Science and the College of Education. To achieve the research objectives, the researcher adopted the scale of Brown & Hegarty (2021) based on the theory of social information processing by Joseph Wallace (1992). After it was translated into Arabic, it consisted of 25 items. The results showed that students at Al-Mustansiriya University are characterized by misuse of technology in electronic relationships, i.e., online dating. There are statistically significant differences according to gender in favor of males; this implies that males are more misusing technology in electronic relationships. There are no statistically significant differences according to the variables of specialization and grade. The means of social media (Facebook, Instagram, and Twitter) were the most used among young people. The researcher made several recommendations and suggestions.